Mitochondrial genomes of blister beetles (Coleoptera, Meloidae) and two large intergenic spacers in Hycleus genera - Chao Du (BMC Genomics, 2017)
Abstract Background Insect mitochondrial genomes (mitogenomes) exhibit high diversity in some lineages. The gene rearrangement and large intergenic spacer (IGS) have been reported in several Coleopteran species, although very little is known about mitogenomes of Meloidae. Results We determined complete or nearly complete mitogenomes of seven meloid species. The circular genomes encode 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs) and two ribosomal RNAs (rRNAs), and contain a control region, with gene arrangement identical to the ancestral type for insects. The evolutionary rates of all PCGs indicate that their evolution is based on purifying selection. The comparison of tRNA secondary structures indicates diverse substitution patterns in Meloidae. Remarkably, all mitogenomes of the three studied Hycleus species contain two large intergenic spacers (IGSs). IGS1 is located between trnW and trnC, including a 9 bp consensus motif. IGS2 is located between trnS2 (UCN) and nad1, containing discontinuous repeats of a pentanucleotide motif and two 18-bp repeat units in both ends. To date, IGS2 is found only in genera Hycleus across all published Coleopteran mitogenomes. The duplication/random loss model and slipped-strand mispairing are proposed as evolutionary mechanisms for the two IGSs (IGS1, IGS2). The phylogenetic analyses using MrBayes, RAxML, and PhyloBayes methods based on nucleotide and amino acid datasets of 13 PCGs from all published mitogenomes of Tenebrionoids, consistently recover the monophylies of Meloidae and Tenebrionidae. Within Meloidae, the genus Lytta clusters with Epicauta rather than with Mylabris. Although data collected thus far could not resolve the phylogenetic relationships within Meloidae, this study will assist in future mapping of the Meloidae phylogeny. Conclusions This study presents mitogenomes of seven meloid beetles. New mitogenomes retain the genomic architecture of the Coleopteran ancestor, but contain two IGSs in the three studied Hycleus species. Comparative analyses of two IGSs suggest that their evolutionary mechanisms are duplication/random loss model and slipped-strand mispairing.